Production yearbook - Erus, N.; Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations., 1959)
This is the thirteenth issue of the Production Yearbook. It contains annual data on all important aspects of food and agricultural production, food supplies, prices, wages and freight rates.
Ref
osa 25/01/2019
Keywords: Agriculture; Statistics, Agricultural